A novel progressive collapse design concept for structural systems based on regional behaviors. (1st October 2022) - Zhong, Wei-hui; Zheng, Yu-hui; Tan, Zheng; Meng, Bao; Duan, Shi-Chao
Abstract: To actively control the failure mode of structural systems, an anti-collapse design method considering the interaction between structural regions, called the region sacrifice (RS) method, is proposed in this paper. This approach divides a steel frame into regions separated by partition frames designed to prevent the transmission of failure response throughout the structure while ensuring structural stability. The transmission of the failure response through a steel frame structural system was investigated by considering the instability of the columns as a typical critical failure mode. The spatial effect of the unbalanced load resulting from column failure on the stability bearing capacity of adjacent columns was transformed into two plane load effects (unbalanced moment and horizontal tie force). The maximum collapse load for considering the most adverse effects of unexpected loads was then calculated based on this plane calculation model, and the most adverse impact of the sacrificed region on the other regions was considered using this load. Then, based on the relationship between different load effects and the ultimate stability bearing capacity of the adjacent regional edge columns, partition frames were designed to prevent the transmission of failure beyond the sacrificed region. Finally, detailed design strategies were obtained that can be used for any region partition scheme. Based on an analysis of reliable examples, the RS method was shown to prevent the structural failure from crossing beyond the sacrificed region. Notably, after the columns in the sacrificed region lost their stable bearing capacity, the adjacent regional edge columns still exhibited a certain capacity. Thus, the design concept underlying the RS method provides a new approach for the anti-collapse design of structures. Highlights: A novel design concept (region sacrifice method) was proposed. Structures with controllable failure mode were designed. Detailed design strategies were provide. Chain failure action was blocked.